2016
DOI: 10.1002/cld.586
|View full text |Cite
|
Sign up to set email alerts
|

How does the microbiome affect liver disease?

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/8-5-reading-tilg.html a video presentation of this article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Dysbiosis of the intestinal microbiome is a known feature of alcohol-induced cirrhosis. Bifidobacteria, Streptococci, Veillonella and Enterobacteria were found to be elevated in cirrhosis, whereas Faecalibacterium showed a reduction [ 58 , 76 , 78 ]. In our cohort, we could observe reduced diversity, and on a genus level, also increased abundance of Veillonella compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis of the intestinal microbiome is a known feature of alcohol-induced cirrhosis. Bifidobacteria, Streptococci, Veillonella and Enterobacteria were found to be elevated in cirrhosis, whereas Faecalibacterium showed a reduction [ 58 , 76 , 78 ]. In our cohort, we could observe reduced diversity, and on a genus level, also increased abundance of Veillonella compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that microbiota is changed in liver disease 28 and associated pathologies such as non-alcoholic fatty liver disease (NAFLD), cirrhosis 28 , type 2 diabetes and obesity 29, 30 . Different studies reported associations between Verrucomicrobia and liver related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Compositional shifts in the gut microbiota are linked with liver disease 1 , 2 . In liver cirrhosis (LC), the alteration in gut microbiota is characterized by an overgrowth of potentially pathogenic bacteria and a decrease in beneficial commensal species 3 .…”
Section: Introductionmentioning
confidence: 99%